2022
DOI: 10.30574/wjarr.2022.14.1.0344
|View full text |Cite
|
Sign up to set email alerts
|

Haematological and behavioral response of African catfish (Clarias gariepinus) (Burchell, 1822) exposed to sub-lethal concentration of xylene

Abstract: The study was carried out to examine the haematological and behavioral response of African catfish (Clarias gariepinus) exposed to sub-lethal concentrations (0.0 ml/L (as control), 12.8 ml/ L, 25.59 ml/L, 38.39 ml/L, 51.19 ml/L, and 63.99 ml/L) of xylene using a renewable assay for 28 days. A total of one hundred and twenty (120) healthy Clarias gariepinus with a mean length of 15.20±2.3 cm and mean weight of 10.23±2.60 g was used for the experiment. Some physicochemical parameters such as temperature, conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…The observed variations in the haematological parameters of blood cells may because anemia and leucopenia as reported by (Luskova et al 2002 ). These results were in agreement with Chris et al ( 2022 ), who observed decreased in RBCs, HB, Hct, Platelets and MCHC and increased in MCV and WBCs in Clarias gariepinus when exposed to different doses of xylene.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The observed variations in the haematological parameters of blood cells may because anemia and leucopenia as reported by (Luskova et al 2002 ). These results were in agreement with Chris et al ( 2022 ), who observed decreased in RBCs, HB, Hct, Platelets and MCHC and increased in MCV and WBCs in Clarias gariepinus when exposed to different doses of xylene.…”
Section: Discussionsupporting
confidence: 93%
“…The changes observed in fish Hct can be attributed to the swimming frequency resulting from the increased concentration level of the toxicant, significant decline in the RBC, Hct, and hemoglobin due to the increasing doses of xylene (Chris et al 2022 ). This agrees with Valores, (2005) who reported a low level of Hct and hemoglobin in an aquatic organism with sedentary behavior in some lentic water bodies and a higher value in active aquatic lives with spleen contraction which also resulted in a distorted shape and size of RBC as well (Dal'Bó et al 2015 ; Gallo et al 2017 ; Wilhelm et al 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…The declining opercular beat frequency indicates a deteriorating respiratory function, which can be attributed to the accumulation of surfactant-induced damage to the gills and associated respiratory structures. 33 Overall, the observed variations in opercular beat frequency at different surfactant concentrations and exposure times provide evidence of the detrimental effects of surfactants on T. guineensis. The increased opercular beat frequency initially indicates a compensatory response to maintain adequate oxygen uptake, while the subsequent decrease reflects the fish's inability to withstand prolonged exposure to the toxicants.…”
Section: Opercular Beat Frequency (Obf)mentioning
confidence: 83%
“…This indicates that the absence of surfactant exposure did not cause any significant disruption to their normal swimming patterns or responses to the environment. 33 Initially, the fish exposed to 0.0 ml/L surfactant concentration showed normal behaviour for 24 to 96 h. However, after this period, they exhibited a response to sudden changes in the surrounding environment by becoming static for a while. This behaviour suggests heightened alertness or a cautious response to potential threats or disturbances.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation